Comparative study of radiation-based reference evapotranspiration models for tropical urban region - Muhamad Askari; Umar Faruk Lawan; Jazaul Ikhsan; Mohd Remy Rozainy Mohd Arif Zainol; Nor Azazi Zakaria (Springer Nature, 2024)
Estimation of reference evapotranspiration (Eto) using the FAO Penman– Monteith model become more popular in developing countries. However, it involves complete weather variables data. In order to provide an alternative solution, we evaluated twenty-one radiation-based Eto models against 20-years observed pan evaporation data from Subang meteorological station, Malaysia. To fill the missing data was based on Julian day-based mean imputation. Outlier was tested using Tukey’s detection method prior to estimating the Eto. The percentage of error (% error) in total values, % error in maximum values, % error in minimum values, % error in average values, root mean squared error (RMSE), and the paired t-test of the prediction accuracy were employed to evaluate the performance of the models. The results showed that the Cochrane-Orcutt 2014 model was performed better than the other radiation-based Eto models. The present study recommended the Cochrane-Orcutt 2014 model as the possible alternative Eto model for practical hydrological application according to the smallest difference of RMSE values as compared to the ETpan and due to the less number of required weather variables.